The Role of Forum Discussion in the Online Learning Modality of Senior High School Students - Renato Tiria; Mary Ann Ferrer; Lilibeth Caballero; Jenny Verzosa (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2022)
The new normal has brought changes in the teaching-learning platform. Different modalities are implemented to ensure the continuation of education, but some nations had decided to close their educational system while amidst the pandemic. The Philippines have decided to enter the synchronous and asynchronous modality of learning. This study aimed to know the role of online recitation through forum discussion in the synchronous learning modality. Thirty grade 11 STEM students were chosen purposively for this study. Google Classroom was the online platform used by the researchers, the classwork section of the google classroom was utilized where questions were posted, and responses were placed by the students. Rubric scoring was used to grade the works of students. The result of the study showed that there is no significant difference in the performance of students in terms of participation, quality of posts, plagiarism, and students' attitudes.